2021
DOI: 10.3390/nano11112867
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Cross-Linked Graphene Oxide as a Selective Layer on Electrospun Polyvinyl Alcohol Nanofiber Membrane for Nanofiltration Application

Abstract: Graphene oxide (GO) nanosheets were utilized as a selective layer on a highly porous polyvinyl alcohol (PVA) nanofiber support via a pressure-assisted self-assembly technique to synthesize composite nanofiltration membranes. The GO layer was rendered stable by cross-linking the nanosheets (GO-to-GO) and by linking them onto the support surface (GO-to-PVA) using glutaraldehyde (GA). The amounts of GO and GA deposited on the PVA substrate were varied to determine the optimum nanofiltration membrane both in terms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…Overall, we confirmed that DCX crosslinking can contribute to improving the salt-rejection efficiencies of GO membranes. To further evaluate the effect of DCX crosslinking, we also compared the NF performance of our DCX/GO membranes by benchmarking the Na 2 SO 4 rejection and the PWP performances of previously reported crosslinked GO membranes ( Figure 10 and Table S3 ) [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. The results revealed that our GO/DCX membranes outperformed other crosslinked GO membranes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, we confirmed that DCX crosslinking can contribute to improving the salt-rejection efficiencies of GO membranes. To further evaluate the effect of DCX crosslinking, we also compared the NF performance of our DCX/GO membranes by benchmarking the Na 2 SO 4 rejection and the PWP performances of previously reported crosslinked GO membranes ( Figure 10 and Table S3 ) [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. The results revealed that our GO/DCX membranes outperformed other crosslinked GO membranes.…”
Section: Resultsmentioning
confidence: 99%
“… Performance comparison plot showing the Na2SO4 rejection efficiencies and the PWP of GO-based NF membranes, including our GO membranes [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…A vacuum ltration unit (dead end ltration) was used to analyze the water permeability and MPs rejection capacity of the fabricated membrane. Before permeance testing, all samples were operated for 15 min by using DI feed water to reduce the impact of membrane compaction on membrane activity(Park, Nisola et al 2021). Here the following equation was used to analyze membrane permeability(Du, Huang et al 2020).…”
mentioning
confidence: 99%
“…J = V A × t × P 2In this equation, J is representing the permeate ux while V, A, t, and P are highlighting the volume of permeate water, effective surface area of membrane, tine duration, and transmembrane pressure respectively. Regarding the evaluation of MPs rejection capacity, following equation was used during experimentation(Park, Nisola et al 2021).R(%) = 100 × 1 − Cp Cf3In this equation, R is representing the MPs rejection rate while Cp and Cf are the permeate concentration and feed concentration respectively.…”
mentioning
confidence: 99%